The Numerical Phenetic of Taxonomy Vibrio in Shellfish (Meretrix meretrix) at Edu-Tourism Mangrove Cengkrong Beach Trenggalek - Burhanuddin Ihsan; Endah Retnaningrum (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightIdentify the Vibrio bacteriaDiversity of shellfish Vibrio bacteria (Meretrix Meretrix)Relationship similarity of Vibrio bacteria with MVSP 3.1 Program produces DendogramAbstract Meretrix meretrix is one type of shellfish that is potential, and economic value, which high animal protein content as well as seafood that is widely consumed in Indonesia. This study aims to determine the diversity and similarity of Vibrio in M. meretrix at eduwisata mangrove Cengkrong Beach, Trenggalek. Isolation and identification of Vibrio was conducted by using the media TCBSA (Thiosulfate Citrate Bile Salt Sucrose Agar) streat plate through morphological observation, physiological and biochemical tests based Bergey's Manual of Systematic Bacteriology conducted in the laboratory of Microbiology Faculty of Biology, Universitas Gajah Mada. Data analysis was performed using the MVSP (Multivariate Statistical Package) 3.1 in the form of a dendrogram showing the similarity relationship Vibrio bacteria. The results of the identification of Vibrio bacteria in M. Meretrix are V. herveyi, V. parahemolyticus, V. nereis and V. proteolyticus. V. herveyi has similarities with V. parahemolyticus 66% and 62% with V. proteolyticus while with V. nereis bacterium 54%.